Protective effects of ginsenoside Rg2 and astaxanthin mixture against UVB-induced DNA damage - Chung, Yu Heon; Jeong, Seul A.; Choi, Hyun Seok; Ro, Seungil; Lee, Jung Sup; Park, Jong Kun (Animal cells and systems, 2018)
Ultraviolet B (UVB) radiation induces skin damage, skin matrix degradation, and wrinkle formation through photochemical reaction and oxidative stress. Therefore, protecting the skin from UVB can prevent skin aging. In this study, we investigated the effects of a mixture (RA) of Rg2, a ginsenoside, and astaxanthin, an antioxidant, on the responses of HaCaT cells exposed to UVB (700 J/m 2 ). The cells were incubated for 24 h after UVB exposure and cell viability was determined by MTT assay. UVB decreased cell viability by 60% compared to that of untreated control cells, whereas RA increased cell viability in a concentration-dependent manner, and this increase was significantly higher than that in the single treatment groups. Further, UVB increased the levels of DNA lesions such as cyclobutane pyrimidine dimer (CPD) and 8-hydroxyguanine (8-OHdG). Conversely, RA decreased both CPD and 8-OHdG levels in a concentration-dependent manner. UVB exposure also increased phosphorylation of ataxia-telangiectasia mutated (ATM) protein kinase and p53 and subsequently increased the levels of GADD45α, p21, and matrix metalloproteinases (MMPs)-3, -9, and -13. Additionally, UVB exposure decreased the level of COL1A1. However, RA treatment decreased the levels of p-ATM, p-p53, GADD45α, p21, MMP-3, -9, and -13 and increased the level of COL1A1 in a concentration-dependent manner. These results suggest that RA reduces UVB-induced cytotoxicity and genotoxicity through up-regulation of DNA repair via the combined effects of Rg2 and astaxanthin.